Re-Envisioning Organizations Through Transformational Change A Practitioners Guide to Work, Workforce, and Workplace. - Madan, Poornima; Tripathi, Shruti; Khalique, Fehmina; Puri, Geetika (Milton : Productivity Press, 2022)
The journey towards the future of work was greatly accelerated due to the COVID pandemic. Some changes have altered the functioning of the business world forever. Against the backdrop of these alterations, variations, and modifications, this book presents and analyzes three crucial factors: work, workforce, and workplace and their transformation into new-age organizations for meeting its customer expectations and long-term strategic goals. Companies must focus on ways of deployment of policies and practices that meet the business needs from the perspective of external changes. To achieve this goal, the organizations must realign their stakeholders and indulge in critical thinking by looking deeply into factors responsible for bringing about this transformational change. Re-envisioning is the current critical need for organizations to thrive; they must incorporate best practices to beat the competition and add value to their existing HR processes. This book clearly presents the practices and policies of successful organizations through the contribution of industry leaders. This book helps you understand the dynamism of work, workforce, and workplace that exist in organizations (as well as the challenges these organizations face) and their impact on business practices. The authors cover these broad areas because of the need to diversify and promote organic inclusive growth. Essentially, re-envisioning our organizations is the new normal. Organizations must leave the shackles of what might have been and look to what they can be. Stakeholders, employees, and the environment have been drastically altered, and organizations must change accordingly to survive. What now matters is how much an organization re-envisions itself and how it deals with all that is happening.
5. The Genius of Craft Brewing: Case of Third Generation Brewing Entrepreneur of Pune -- SECTION III: WORKPLACE -- 6. HR Transformations in Turbulent Times: A Progressive Paradigm Shift -- 7. Workforce Shift after COVID-19 Outbreak: Adapting to Evolving Workplace and Work-Life Settings -- 8. Rebuilding Organizations Post-Pandemic -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Management; Organizational behavior; Organizational change; Business enterprises; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Human Resources & Personnel Management